Caracterización de la familia poaceae presentes en el campus salache de la universidad técnica de Cotopaxi. - Luis Fernando, Coello Mora (2020)
At the present work the Poaceae research of Salache campus of Technical University of Cotopaxi was carried out. To get this objective, a floristic inventory of study area, digital review of physical, and botanical specimens including a bibliographic revision were made. For this project the herbarium of Technical University of Cotopaxi (UTCEC) and Herbarium of Catholic Pontifical University of Ecuador (QCA) were consulted; in addition, samples from the digital Herbarium of tropics.org were added. As result agrostological flora of Cotopaxi Province is constituted by 75 genera and 205 species, being Clamagrostis with 18 species, Festuca and Poa (17) the most representative taxa. Latacunga canton (57%) is the town with the highest number of records in the province. From Salache campus inventory, 10 genera and 10 species are reported, with Bromus catharticus Vahl being the most frequent taxon in sampling, followed by Agrostis sp. The species with the lowest number of samples were Holcus lanatus L, Lolium multiflorum Lam and Briza maximum L, it must be taking into count that the greatest area diversity of species was the low zone with 8 genera and 6 species, while the mountainous area registered the lowest number of taxa. In conclusion, the province's agrostological flora is scarcely realized. Similar studies are recommended for the province.